3, 5-Bis(3-dimethylaminomethyl-4-hydroxybenzylidene)-4-piperidone and related compounds induce glutathione oxidation and mitochondria-mediated cell death in HCT-116 colon cancer cells. Issue 16 (15th August 2017) - Addala, Eshwari; Rafiei, Hossein; Das, Swagatika; Bandy, Brian; Das, Umashankar; Karki, Subhas S.; Dimmock, Jonathan R.
Graphical abstract: Abstract: This study aims at investigating the cytotoxicity and some of the modes of action of 3, 5-bis(3-dimethylamino-4-hydroxybenzylidene)-4-piperidone trihydrochloride 3 and two related compounds 2 (which lacks the dimethylaminomethyl groups) and 4 (which has an additional dimethylaminoethyl substituent in both aryl rings) in order to ascertain the contribution of dimethylaminoethyl substituent to bioactivity. The bioactivities of 2 –4 were compared with curcumin 5 . Both 2 and 3 displayed submicromolar GI50 values towards HCT-116 cells and were significantly more potent than 4, 5 and 5-fluorouracil (5-FU). All of the compounds displayed greater toxicity towards HCT-116 cells than human CRL-1790 non-malignant colon cells. In HCT-116 cells, the compounds 2, 3 and 5 increased the ratio of oxidised to reduced glutathione and destabilized the mitochondrial membrane potential. Both 2 and 5 produced an increase in mitochondrial superoxide and a burst in intracellular reactive oxygen species in HCT 116 cells. In addition, 2 and 4 stimulated respiration in rat liver mitochondria while 2 and 5 induced mitochondrial swelling. The results suggest that 2 and 5 cause oxidation or cross-linking of the thiols which control the mitochondrial permeability transition.